Muhammadiyah Education Trilogy: Knowledge, Faith and Charity - Kurniawan, Ade Habib Muhammad; Maksum, Muh. Nur Rochim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Contemporary Islamic education faces challenges in the form of a dichotomy between religious science and general science, weak character development, and the demand for adaptation to the development of science and technology. Muhammadiyah responds to these challenges through the concept of the Education Trilogy which emphasizes the integration of faith, knowledge, and charity as a paradigm of progressive Islamic education. This research aims to analyze the basic concept of the Muhammadiyah Education Trilogy, its form of integration in educational practices, and its differences with the paradigm of secular education and traditional Islamic education. This research uses a qualitative approach with the type of library research. Data were obtained from academic books, national and international journal articles, as well as relevant scientific sources that discuss Islamic education, Muhammadiyah education, and contemporary education issues. Data analysis is carried out through content analysis techniques. The results of the study show that the trilogy of faith, science, and charity is a holistic foundation that forms a balance between the spiritual, intellectual, and social dimensions of students. Faith functions as the foundation of values and ethical orientation, science as a means of developing thinking capacity and mastery of science and technology, while charity is a real actualization of faith and science in the form of morals and social actions. Compared to secular education which tends to emphasize cognitive aspects and traditional education that is less responsive to the dynamics of the times, Muhammadiyah education offers an integrative, contextual, and transformative approach. Thus, the Muhammadiyah Education Trilogy has strong relevance as an Islamic education paradigm that is able to answer the challenges of modern education and encourage the realization of progressive Islamic civilization.